Stres dalam kalangan penduduk dewasa luar bandar,daerah Hulu Langat,Selangor. - Jamsiah M,; Rosnah S,; Noor Hassim I, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Background : Study of stress among adults in rural community is seldom been conducted and this study aims to see the prevelence of the stress among this group of population. Methodology : A cross sectional study was conducted to measure the prevalence of stress among the rural people in Hulu Langat District, Selangor using O`Donnell Personal Stress Inventory and coping mechanism practiced by them. Result : A total of 265 respondents through universal sampling participated in this study. The stress prevalence identified was 16.2%. The factors which have significant association with stress were age, education level, marital status, working women, duration of working per day and body mass index. Diseases such as diabetis mellitus and hypertension showed no association with stress. Preferred coping mechanism used by respondents included emotional support, instrumental support, behaviour modification and denial. Conclusion : Stress among the rural population is high in Malaysia. Measures has to be taken to reduce the stress as it can effect the general health of the people.